Time-of-Day could affect cognitive screening performance in older patients with TIA and stroke - Mazzucco, S; Li, L; Tuna, M; Pendlebury, S; Frost, R; Wharton, R; Rothwell, P (karger, 2017)
Background and Purpose The impact of time-of-day on the cognitive performance of older patients with limited cognitive reserve after a transient ischemic attack (TIA) or stroke, and on short cognitive tests, such as the Montreal Cognitive Assessment (MoCA), is unknown. We retrospectively studied whether morning versus afternoon assessment might affect the classification of patients aged 70 or older as severe (SCI), mild (MCI), and no (NCI) cognitive impairment by the MoCA. Methods Morning (12 p.m. or earlier) versus afternoon (later than 12 p.m.) proportions of SCI (MoCA score <20), MCI (MoCA score 25–20) and NCI (MoCA score ≥ 26) were compared in a cohort of patients aged ≥ 70, attending a rapidaccess TIA/stroke clinic. Results Of 278 patients, 113 (40.6%) were tested in the morning and 165 (59.4%) in the afternoon. The proportion with SCI was greater in the afternoon than in the morning (10.9 vs. 1.8%, respectively, p = 0.004), with no difference in age, education, diagnosis, disability, or vascular risk factors. Conclusions Time-of-day appears to affect cognitive performance of older patients after they undergo TIA and minor stroke. If our cross-sectional findings are confirmed in cross-over studies with repeated testing, timing of assessments should be considered in clinical practice and in research studies.